Thermodynamic description of the Mg-O and Al-O systems - Li X.-J.; Liu S.-H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The thermodynamic properties of oxides have a considerable influence on the corrosion behavior of alloys. MgO and Al2O3 are important products in the corrosion process of Mg-Al alloys, therefore it is necessary to investigate their thermodynamic properties. The Mg-O and Al-O systems were critically evaluated and re-evaluated using the CALPHAD (CALculation of PHAse Diagram) approach. The liquid phases of these systems were described using the ionic liquid model. According to the literature data, the oxide phases, MgO and Al2O3 were treated as stoichiometric compounds. The thermodynamic parameters of the two stoichiometric compounds were optimized considering both the phase diagram and the thermodynamic data, and finally a set of self-consistent thermodynamic parameters was determined for each system. The calculated results using the presently obtained thermodynamic parameters can reasonably reproduce the reliable experimental data in the literature.